(untitled) (Journal of Pure and Applied Sciences (Science Forum), 2026)
Nigeria, the most populated country of Africa is reactivating her coal industry as a sup plementary energy source. Bukan—Kwato coalfield is one of the recently discovered coal deposits in Lafia that is receiving great attention from investors and entrepreneurs of coal energy. The coal serves as the prime target for power generation by the Nigerian Government, yet little is known about the basic properties of the deposit. The research seeks to achieve the objectives of collection of fresh coal samples from the mining site, so as to carry out the chemical analysis, determine the calorific value, and suggest the best methods for processing coal. The coal samples were collected from the study area and were subjected to proximate, ultimate, and calorific value determination in order to determine the intrinsic properties of the coal. Proximate analysis was carried out on pul verized samples using the Muffle furnace, carbon and hydrogen were determined using the method described in the Liebig method while nitrogen was obtained using the Kjeldahl method. The sulfur content was obtained using the ESCHKA method and the oxygen con tent was calculated by difference on an air-dried basis. Calorific value was determined using the isoperibol calorimeter. The results obtained compared with the standard pulver ized coal fire plants show that the coal has a medium-to-high carbon content of 54.68%, high moisture content of (9.72%), nitrogen (3.5%), sulfur (24.24%), and ash (31.74%) with a corresponding low volatile matter of 20.28%. The high ash content in the coal can be used as thermal coal for power generation.